Enhancing Students’ Motivation and Proficiency on Technical Vocabulary through Flipped Learning - Ariani, Desti; Jayanti, Ade Dwi; Hidayat, Ade; Irawan, Bayu Putra (LPPM Politeknik Raflesia, 2024)
Having sufficient English vocabulary especially the technical one indeed becomes one of the aspects in supporting the English learning for Electrical Engineering students. This classroom action research study, therefore, aims to investigate students’ motivation and proficiency on technical vocabulary through the implementation of Flipped Learning. This study was conducted to the second semester students of Electrical Engineering Study Program of Polytechnic of Raflesia. The Flipped Learning was implemented in two cycles consisting of four meetings of each cycle. Pre-test and post-test were given along the learning to assure the improvement on students’ vocabulary. The interview then was conducted as well to figure out how Flipped Learning influenced students’ motivation. The study reveals that Flipped Learning does contribute positively to the students’ motivation and their proficiency on Technical Vocabulary, especially on noun and verb related to the safety precaution and safety equipment.